Dynamics of Aboveground Natural Enemies of Grasshoppers, and Biodiversity after Application of Paranosema locustae in Rangeland - Wang-Peng Shi; Xiao-Yu Wang; Yue Yin; Yu-Xing Zhang; Um-e-Hani Rizvi; Shu-Qian Tan; Chuan Cao; Hong-Yan Yu; Rong Ji (Insects, 2019)
Substantial harm to ecosystems from the use of chemical pesticides has led to an increasing interest in the use of biopesticides to control grasshoppers in rangelands, including China. One such potential biopesticide for control of grasshoppers is the fungus Paranosema locustae. In this study, the dynamics of aboveground natural enemies of grasshoppers and arthropod diversity 0−9 years after application of P. locustae were investigated in rangeland in Qinghai Plateau, China. We found that the number of species and of individuals of aboveground natural enemies increased by 17−250% and 40−126%, respectively, after spraying P. locustae, and that the main natural enemies showed three peaks after treatment. The conventional indices of species diversity (H’) and evenness (J’) increased by 11−267% and 13−171%, respectively, after treatment with P. locustae. The results showed the positive effects of P. locustae on aboveground natural enemies and biodiversity in an arthropod community in Chinese rangeland. Paranosema locustae is thought to be a safe biological control agent for grasshopper management in Northwestern China.